Supercontinuum Generation in Naturally Occurring Glass Sponges Spicules. Issue 10 (8th July 2016) - Ehrlich, Hermann; Maldonado, Manuel; Parker, Andrew R.; Kulchin, Yuri N.; Schilling, Jörg; Köhler, Benjamin; Skrzypczak, Ulrich; Simon, Paul; Reiswig, Henry M.; Tsurkan, Mikhail V.; Brunner, Eike; Voznesenskiy, Sergey S.; et al.
Abstract : The complex process of supercontinuum generation (SG) is known to be exploitable for designing spatially coherent white light sources emitting light simultaneously in the ultraviolet, visible, and infrared ranges. Herein the first natural material able to generate in laboratory conditions a supercontinuum similar to those known from man‐made photonic crystal fibers is described. The ability resides in siliceous 20–50 cm long spicules of the glass sponge Sericolophus hawaiicus . By shedding into the spicules optical peak intensities ranging from 1 to 100 TW cm −2 the generation of a SG is revealed. The SG involves wavelengths between 650 and 900 nm and shows a maximum spectral spread for excitation at a wavelength of 750 nm. It is hypothesized that the SG is favored by spicules being a biocomposite that incorporates together isotopically pure biogenic silica ( δ 30 Si = −3.28) and 15.2 ± 1.3 μg N ‐acetyl‐glucosamine (chitin) per mg of silica. The internal organization of these spicules is distinguished by a solid silica core with a 1 μm wide axial channel as well as a highly ordered silica–chitin composite. Such a composition and organization pattern may be of potential interest for the design of low temperature synthesis of future materials for light guidance. Abstract : The anchoring spicules of Sericolophus hawaiicus represent a unique biocomposite containing biosilica within specifically structured nanolamellar chitin. The generation of supercontinuum in these naturally occurring fibers is demonstrated for the first time. In contrast to in range between 1000 and 2000 °C artificially synthetized fibers with supercontinuum properties, glass sponges produce siliceous spicules with similar features at temperatures around 4 °C.